Does Electroacupuncture Have Different Effects on Peripheral and Central Sensitization in Humans: A Randomized Controlled Study - Zheng, Zhen; Bai, Linghan; O’Loughlan, Meredith; Li, Chun Guang; Xue, Charlie C. (Frontiers in Integrative Neuroscience, 2019)
Background Acupuncture is used to reduce chronic musculoskeletal pain. The common mechanism underlying these types of pain are peripheral and/or central sensitization. In the clinical setting, it is difficult to separate the peripheral from the central component of pain. Heat/capsaicin 45°C/0.075%-induced hyperalgesia provides a stable, human central sensitization model in which the peripheral component is also assessed. Aim This randomized, sham-controlled study aimed to investigate the effect of electroacupuncture (EA) on the severity of heat (peripheral sensitization) and mechanical hyperalgesia (central sensitization) in a heat/capsaicin pain model in humans. Methods Twenty-six healthy young participants (24 ± 3.9 years) were recruited. After baseline assessment, heat/capsaicin 45°C/0.075% was applied to the non-dominant forearm to induce hyperalgesia. The primary outcome measures were the size of the area of mechanical hyperalgesia, intensity of pain to heat stimulation and heat pain thresholds. The intensity of pain was recorded using modified 10-cm visual analogues scales (VAS). Participants were assessed at 70 min after the initial application of capsaicin then randomly allocated to receive either real electroacupuncture (REA, n = 14) or sham non-invasive EA (SEA, n = 12) for 30 min. The main outcome measures were assessed again immediately and then 90 min following EA. Credibility of blinding was assessed. Data were analyzed with t-tests or analysis of variance (ANOVA) where appropriate. Results After the model was established, the area of mechanical hyperalgesia was formed (55.64 cm2), as was heat hyperalgesia, as the rating to heat stimulation, increased from 2/10 to 6/10. The REA and SEA groups were comparable. Immediately after the allocated acupuncture treatment, the rating to heat stimulation was statistically significantly lower in the REA group (2.94 ± 1.64) than in the SEA group (4.62 ± 2.26) (p < 0.05). The area of mechanical hyperalgesia reduced significantly without any group difference. No group difference was detected in heat pain threshold. Blinding of the participants was successful. Conclusion Peripheral and central sensitization in the heat/capsaicin 45°C/0.075% model responded to EA differently, suggesting that acupuncture analgesia could vary, depending on the types of pain. This observation may explain some inconsistent findings from clinical trials of acupuncture.